Denitrifying anaerobic methane-oxidizing bacteria in river networks of the Taihu Basin: Community dynamics and assembly process - Wang, Ruyue; Xu, Sai; Zhu, Yuxiang; Zhang, Tao; Ge, Shijian (Frontiers in Microbiology, 2022)
Denitrifying anaerobic methane-oxidizing bacteria (DAMO bacteria) plays an important role in reducing methane emissions from river ecosystems. However, its community assembly process underlying different hydrologic seasons remains unclarified. In this study, the dynamics of DAMO bacterial communities in river networks of the Taihu Basin were investigated across wet, normal, and dry seasons by amplicon sequencing followed by multiple statistical analyses. Phylogenetic analysis showed that Group B was the major subgroup of DAMO bacteria and significant dynamics for its community were observed across different seasons (p=0.001). Furthermore, the neutral community model and normalized stochasticity ratio model were applied to reveal the assembly process underlying the dynamics of DAMO bacterial communities. Both deterministic and stochastic processes shaped DAMO bacterial communities, with stochastic process dominating in wet season and deterministic process dominating in other seasons. Meanwhile, abundant (relative abundance >0.1%) and rare (relative abundance <0.01%) DAMO bacterial communities were found to be shaped via distinct assembly processes. Deterministic and stochastic processes played a considerable role in shaping abundant DAMO bacterial communities, while deterministic process mainly shaped rare DAMO bacterial communities. Results of this study revealed the dynamics of DAMO bacterial communities in river networks and provided a theoretical basis for further understanding of its assembly process.